VALIDITY OF HUMAN ANATOMY AND PHYSIOLOGY TEXTBOOKS BASED ON SCIENCE LITERACY - Gultom, Rahmad H; Lubis, Shofia; Pardosi, Sri Masnita; Nasution, Alvi Sahrin (Jurnal Pelita Pendidikan, 2025)
The study aims to validate the textbook of Human Anatomy and Physiology. The validation conducted leads to the analysis of the textbook on scientific literacy, namely to determine the scope of scientific literacy in the textbook. This study is a descriptive study that aims to explain the validation results. This module was validated by three validators. There are four components that validated, namely content validity consisting of module components and the suitability of module content, construct validity, language validity, and suitability with learning that uses conceptual changes. The results of the validation of human anatomy and physiology materials for semester VI Biology students at Medan State University found that the standards for human anatomy and physiology teaching materials based on scientific literacy have met the Very Good category with a percentage score and an average number of feasibility: Content feasibility is 88.67, presentation feasibility 93%, feasibility of scientific literacy components 93%. The results of the study concluded three textbooks used in university emphasize more on the presentation of facts, concepts, principles, laws, theories and models and emphasize that students can remember information through questions.